Genetic Parameters for Traits in Acacia nilotica Willd. (Babul) - Dar, M. Ayoub; Nautiyal, S.; Bakshi, Meena; Mazher, Farheen (Indian Forester, 2010)
Genetic parameters for nine pod and seed traits and per cent germination were worked out in thirty seed sources of Acacia nilotica mostly from the State ofHaryana, Himachal Pradesh and Punjab. Values for variahility in expected genetic gain were calculated for all individual characters. Seed length, seed width and 100 seed weight exhibited high genetic variability, heritability and genetic gain. Correlation study reveled that pod thickness; pod weight, seed length, seed width, seed thickness and 100 seed weight had significant and positive association with germination percentage. These traits, therefore should be given priority for improving germination in Acacia nilotica.